Compilation of Accounting System at Nurul Hikmah Mosque Based on Microsoft Excel - Oktavian Y, Aulia Eka; Pahala, Indra; Khairunnisa, Hera (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
The preparation of an effective accounting system is needed by organizations in Indonesia in suppressing problems caused by growth and uncertainty experienced so far. The research aims to describe the accounting cycle and compile an accounting system. The research method used is a descriptive method with a qualitative approach and the type of data used is primary data and secondary data. Primary data was obtained through interviews with the management of the Nurul Hikmah Mosque. Secondary data went through the documentation process during field observation at the Nurul Hikmah Mosque. Data analysis is carried out using the Model Framework For The Application of System Thinking (FAST) which can develop information system systems. The result of this research is a prototype or design of a mosque financial report information system based on Microsoft Excel. The results of this research can then be a reference for the development of information systems in compiling Nurul Hikmah Mosque financial reports.